Moringa Leaf Extract (Moringan Oleifera) and Honey Improve The Levels of Haemoglobin in Norvegicus Rattus that Suffer Anemia - Ratna Hidayati; Efa Nur Aini; Devita Anugrah Anggraini (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2021)
Abstract Background : Anemia decreases concentration in learning, decreases physical ability, work productivity, and thinking ability in adolescents. The purpose of this study was to prove the difference in effectiveness of the administration of Moringa oleifera leaf and honey to hemoglobin levels in anemia. Methods: This study used the true experimental design with the post test only control group design method, in 21 rats selected through random sampling technique divided into 3, namely 7 moringa leaf extract groups, 7 honey groups, and 7 control groups. The variable measured in this study was the difference in hemoglobin levels after intervention. This study uses the independent statistical test T-test. Results: The results of the study in all 100% treatment groups experienced a significant increase in hemoglobin levels with an average post test score for Moringa leaf extract 18.17 g / dl higher than honey supply with an average score of 17.57 g / dl. Based on the Independent T-test analysis, p-value = 0.016 was obtained so that there were differences in the effectiveness of Moringa leaf extract and honey on hemoglobin levels. While Moringa leaf extract is more effective than honey in the treatment of iron deficiency anemia. Conclusion: This is because Moringa leaves contain iron compounds, vitamin C, and folic acid which can increase hemoglobin levels. Meanwhile, honey contains Fe minerals and is rich in vitamins which can increase the number of erythrocytes/Hb levels